Efektivitas Daun Salam (Syzygium Polyanthum) Terhadap Penurunan Tekanan Darah: Literature Review dan Relevansinya Pada Ibu Nifas - Sri Murniyati; Marsum Marsum; Irmawati Irmawati (Jurnal Ners, 2026)
Hypertension during the postpartum period requires safe and effective treatment, including through complementary therapy. Bay leaves (Syzygium polyanthum) are one of the non-pharmacological therapies that have the potential to lower blood pressure through vasodilatory and antioxidant effects, this study aims to identify the effectiveness of bay leaves in lowering blood pressure in postpartum mothers. The method used in this literature review uses the PICO Technique including: Population: postpartum mothers; Intervention: bay leaves; Comparison: standard therapy or not given bay leaves; Outcome: reduction in systolic and diastolic blood pressure. The database used is Evidence Based Practice (EBP) from the Google Scholar and PubMed databases. The results of the study showed that there were 8 articles that mentioned several bay leaf preparations that could be used as a basis for implementing complementary therapy for blood pressure in pregnant women, in adults both men and women and the elderly. It was concluded that the literature search showed that there had not been any research specifically evaluating the effectiveness of bay leaves on blood pressure in postpartum mothers. So it is hoped that these findings will remain relevant for analysis as a scientific basis for complementary therapy for postpartum mothers.